1996
DOI: 10.1115/1.2840938
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling With Compound Angle Holes: Adiabatic Effectiveness

Abstract: The introduction of Lean Burn concept as basic Low-N O x scheme for future aero-engines is heavily affecting the aero-thermal design of combustors. A great amount of air is admitted through the injection system with relevant swirl components, producing very complex flow structures (recirculations, vortex breakdown) for flame stabilization. As a consequence a reduced quantity of air is available for liner cooling, pushing the adoption of high effectiveness cooling schemes. Effusion cooling represents one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
112
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(128 citation statements)
references
References 11 publications
13
112
3
Order By: Relevance
“…Such changes with blowing ratio convince possibilities of different flow patterns of the coolant immediately downstream of injection. These results are qualitatively consistent with the observations made by Schmidt et al [37] and Bell et al [38] for compound angle coolant injection on a flat plate.…”
Section: B Adiabatic and Conjugate Cooling Effectivenesssupporting
confidence: 92%
“…Such changes with blowing ratio convince possibilities of different flow patterns of the coolant immediately downstream of injection. These results are qualitatively consistent with the observations made by Schmidt et al [37] and Bell et al [38] for compound angle coolant injection on a flat plate.…”
Section: B Adiabatic and Conjugate Cooling Effectivenesssupporting
confidence: 92%
“…Schmidt et al [4] and Sen et al [5] presented two companion papers in which the effect of adding a 15° forward diffusion exit to a streamwise oriented hole was investigated. They found that the exit diffused film hole demonstrated better spread of adiabatic effectiveness than the cylindrical counterpart.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Compound angled configurations are also found to resist to lift-off more than simple angled configurations, as reported by Ligrani et al (1994b) and Ekkad et al (1997). Using shaped film cooling holes (with a fan shaped diffuser on the blade surface) results in a smaller tendency to lift off due to the reduction in momentum due to the increase cross sectional area for the coolant, as reported by Schmidt et al (1996) and Gritsch et al (1998).…”
Section: Flat Plate Film Coolingmentioning
confidence: 56%